Islam dan Pendidikan Perempuan - Muhammad, Husein (Jurnal Pendidikan Islam, 2014)
This paper explores the importance of equality in education for women and men. Through historical text review of scholars works in Islamic world from the stories in sahabah era until now in Indonesian era, the writer found that scholars and society’s view about access to education for women as well as women involvement as leaders in political field were varied and dynamic. In part of Islamic history women often perceived as the second class of society while has not equal access to education and self development compared to men. The writer was then elaborated the discussion to Indonesian context. The study concluded that women should be liberated from any kind of oppressions so that they could improve their self potentials. Public policies should be performed to make it possible for women to become experts in their social, politics, and cultural roles besides and together with men.